(untitled) (Research, Society and Development, 2020)
The objective was to perform the physicochemical characterization and sensory acceptance of brownies with functional potential made with alternative flours of brown flaxseed (Linum usitatissimum) and chia flour (Salvia hispânica L.). Brownie formulations were prepared using flaxseed flour (BL) and chia flour (BC), and a traditional formulation using wheat flour (BT). The brownies were analyzed for their physical and physical-chemical characteristics (instrumental analysis of color, water activity, pH, molar acidity, humidity, ash content, determination of fat, protein, total sugars and caloric value), microbiological (determination of coliforms at 45 °C/g, coagulase positive Staphylococcus and research of Salmonella spp. and Bacillus cereus), and sensory (sensory acceptance, purchase intention and relative preference between samples). The results showed that brownies with alternative flours are comparable to other studies found, in terms of physicochemical and microbiological. All brownie formulations scored well in the sensory acceptance test, with emphasis on the BL formulation, which may have had a positive impact on their purchase intention compared to BT and BC. These data were confirmed by the ordering-preference analysis, in which the tasters pointed out BL as the most preferred formulation. Thus, the preparation of brownies using brown flaxseed and chia flour is a viable option for the bakery industry, with great potential in terms of nutritional, functional, microbiological stability and sensory acceptance, and can be introduced into the diet of the general population and individuals with dietary restrictions.